2008
DOI: 10.1002/ijc.23823
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐A2‐restricted CTL epitopes of a novel lung cancer‐associated cancer testis antigen, cell division cycle associated 1, can induce tumor‐reactive CTL

Abstract: Toward the development of a novel cancer immunotherapy, we have previously identified several tumor-associated antigens (TAAs) and the epitopes recognized by human histocompatibility leukocyte (HLA)-A2/A24-restricted cytotoxic T lymphocyte (CTL). In this study, we tried to identify a TAA of lung cancer (LC) and its HLA-A2 restricted CTL epitopes to provide a target antigen useful for cancer immunotherapy of LC. We identified a novel cancer testis antigen, cell division cycle associated gene 1 (CDCA1), overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 35 publications
(56 reference statements)
3
79
0
Order By: Relevance
“…Expression profile analysis demonstrate that NUF2 was overexpressed in various types of cancers including lung cancer, cholangiocellular cancer, urinary bladder cancer, renal cell cancer, colorectal cancer, gastric cancer, ovarian cancer and serous adenocarcinoma (Hayama et al, 2006;Harao et al, 2008;Kaneko et al, 2009;Sethi et al, 2012). Moreover, upregulated NUF2 could predict worse prognosis for patients with non-small cell lung cancer (Hayama et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression profile analysis demonstrate that NUF2 was overexpressed in various types of cancers including lung cancer, cholangiocellular cancer, urinary bladder cancer, renal cell cancer, colorectal cancer, gastric cancer, ovarian cancer and serous adenocarcinoma (Hayama et al, 2006;Harao et al, 2008;Kaneko et al, 2009;Sethi et al, 2012). Moreover, upregulated NUF2 could predict worse prognosis for patients with non-small cell lung cancer (Hayama et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of NUF2 significantly caused cell growth delay and increased apoptosis in cell lines of non-small cell lung cancer, colorectal cancer, gastric cancer and ovarian cancer (Hayama et al, 2006;Kaneko et al, 2009;Sethi et al, 2012). Further study identified NUF2 as a potential cancer testis antigen, and its HLA-A2-restricted cytotoxic T lymphocyte (CTL) epitopes could induce tumor-reactive CTL, suggesting its potential role in diagnosis and immunotherapy of human cancers (Harao et al, 2008). Additionally, alternative splicing variants in NUF2 were also reported to have different expression between cancer cells and corresponding normal tissues (Ohnuma et al, 2009).…”
Section: Silencing Of Nuf2 Inhibits Tumor Growth and Induces Apoptosimentioning
confidence: 98%
“…For example, the expression levels of NUF2 were increased in the majority of small cell lung cancer, cholangiocellular cancer, urinary bladder cancer, and renal cell cancers (45). The MPHOSPH1/PRC1 complex is likely to play a crucial role in bladder carcinogenesis and that inhibition of the MPHOSPH1/PRC1 expression or their interaction should be novel therapeutic targets for bladder cancers (46).…”
Section: Discussionmentioning
confidence: 99%
“…These vaccines were derived from three oncoantigens, URLC10 (also known as LY6K, lymphocyte antigen 6 complex locus K), CDCA1 (cell division cycle-associated protein 1), and KIF20A (kinesin family member 20A). 13,14 Patients' clinical characteristics and outcome are listed in Table 1. Among these five patients, strong CTL responses were detected in patients #1, #3, and #5 by ELISPOT assay along with the ex vivo peptide stimulation, and these patients showed good clinical outcome with prolonged overall survival (OS; average OS D 909 § 278 days).…”
Section: Establishment Of Tcr Sequencing Platform By Ion Torrent Pgmmentioning
confidence: 99%